User needs and the building blocks of regulation: Using participatory design to prototype social enterprise legal structures in Australia. (April 2022) - Moran, Michael; Seibert, Krystian; Barnes, Carolyn; Martin, Fiona
Although co-design is acknowledged as an emerging tool in public administration for use in program or service system design, it has not been widely applied to complex policy spheres, such as law and regulation. In the context of policy development for the field of social enterprise, we explored the use of co-design as a facilitation method to elicit end-users' experience of regulation and to generate options for reform. Specifically, this involved the use of LEGO® Serious Play® to understand end-user views on legal structures following a push by policy advocates in Australia for a structure to serve the needs of social enterprise, similar to that available in the United Kingdom. The article makes two contributions to research on co-design in public policy. The first contribution is methodological. We offer insights into the application of co-design to a new area, law and regulation, finding that co-design is useful for generating bottom-up insights into the regulatory preferences of end-users but has certain limitations as a tool for research and policy development, notably in relation to the feasibility of the insights it may provide. The second contribution is uncovering empirical insights into end-user preferences regarding how regulatory reform might improve the policy environment for social enterprise development in Australia and beyond.